The Frequency of Newly Diagnosed Diabetes Mellitus in Acute Ischemic Stroke Patients - Muhammad Ishfaq, Kalim Ullah Khan, Muhammad Zubair Khan, Asghar Ali, Izhar Ahmad, Naveed Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stroke is ranked as the 3rd leading cause of mortality worldwide and the leading cause of disability in the United States. A diagnosis of diabetes is considered to be an autonomous risk factor for coronary heart disease and stroke. Objective: To find out the frequency of newly diagnosed diabetes mellitus in acute ischemic stroke patients. Method: The current study was descriptive and cross sectional carried out at the Department of General Medicine, MTI-HMC, Peshawar for duration of six months from June, 2019 to December, 2019. In all patients the level of HbA1c levels of was determined in pathology department and their previous records were checked for any history of diabetes or anti diabetic medications. The data was analyzed by using SPSS version 19. Results: In group 1st (40-60) there were 100 (44.05%) acute ischemic stroke patients while in group 2nd (61-80) 127 (55.94%) patients of acute ischemic stroke were recorded. The numbers of male patients were 147 (64.75%) while there were 80 (35.24%) female patients. Mean HbA1c level was observed as 6.2 ±1.44. Newly diagnosed diabetes mellitus was observed in 74 (32.59%) patients. Conclusion: Our study shows that 32.59% acute ischemic stroke patients had newly diagnosed diabetes. Therefore, our research suggests that diabetes mellitus is a common condition in those who have had an acute ischemic stroke. It is suggested that all patients with acute ischemic stroke be diagnosed with diabetes mellitus in order to lower long-term morbidity and death. Keywords: Acute Ischemic Stroke, Newly Diagnosed Diabetes Mellitus, HbA1c.